2022
DOI: 10.1155/2022/7299778
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Applications of Plant-Derived Alkaloids against Inflammatory and Neurodegenerative Diseases

Abstract: Alkaloids are a type of natural compound possessing different pharmacological activities. Natural products, including alkaloids, which originate from plants, have emerged as potential protective agents against neurodegenerative disorders (NDDs) and chronic inflammations. A wide array of prescription drugs are used against these conditions, however, not free of limitations of potency, side effects, and intolerability. In the context of personalized medicine, further research on alkaloids to unravel novel therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 132 publications
(148 reference statements)
0
17
0
Order By: Relevance
“…Previous studies have identified embelin in marine macroalgae, such as Turbinaria species . The presence of alkaloids protects against chronic diseases such as inflammatory and neurogenerative diseases, hypertension, hyperglycemia, and hyperlipidemia, and cholesterol reduction …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified embelin in marine macroalgae, such as Turbinaria species . The presence of alkaloids protects against chronic diseases such as inflammatory and neurogenerative diseases, hypertension, hyperglycemia, and hyperlipidemia, and cholesterol reduction …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified embelin in marine macroalgae, such as Turbinaria species. 78 The presence of alkaloids protects against chronic diseases such as inflammatory and neurogenerative diseases, 79 hypertension, hyperglycemia, and hyperlipidemia, 80 and cholesterol reduction. 81 Plant terpenes metabolites have been shown to have a wide range of biological activities, including cancer chemoprevention, antimicrobial, antifungal, antiviral, antihyperglycemic, anti-inflammatory, and antiparasitic effects.…”
Section: Lc-esi-qtof-ms/ms Characterizationmentioning
confidence: 99%
“…The result of preliminary phytochemical screening revealed the presence of bioactive components such as flavonoids, alkaloids in the test materials of S. argentea. Studies have revealed that alkaloids can block the synthesis of prostaglandin (Aryal et al, 2022;Backhouse et al, 1994), finally dropping raised body temperature in animals. Likewise, flavonoids have been implicated as an antipyretic agent by suppressing TNF-α (Ginwala et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Cyclo-oxygen-ase (COX) is an inflammatory mediator that regulates the inflammatory response and a key rate-limiting enzyme in the initial steps of prostaglandin (PGs) synthesis ( 4 ). PGs have a central role in the induction of the inflammatory response and can be synthesized in inflamed and damaged tissues, thus they are associated with the development of acute inflammatory swelling and painful symptoms ( 5 ). Among them, PGI2 and PGE2 are involved in vascular permeability, tissue swelling and gastric mucus secretion, which are typical symptoms of inflammation ( 6 ).…”
Section: Introductionmentioning
confidence: 99%